SISTEM PENDUKUNG KEPUTUSAN UNTUK KENAIKAN JABATAN MENGGUNAKAN METODE PROFILE MATCHING PADA PETERNAKAN AYAM MANDIRI JAYA FARM - Lucy Simorangkir; Hambali Furnawan; Tonny - (JURNAL AKADEMIKA)
Human resources within an enterprise organization is very important to support the progress and quality of a place of business in achieving its objectives. Promotion is a very important factor for employee career planning and also to rejuvenate a proposed positions. Mandiri Jaya Farm is one of the businesses engaged in poultry which until today still find problems in time will determine whether employees eligible or not to be given a promotion because promotion process is currently only based on factors long worked alone and did not see aspects other. This research aims to develop a decision support system of promotion so it minimizes the error correcting candidate assessment process in order to obtain a more precise and accurate assessment. This system is built using the programming language Visual Basic .NET 2008. The need is employee data input, the data position, variable data, data categories, the data niai, and data calculation profile matching. If the needs of the process in the form of employee data. The output of the report need to determine a suitable employee to gain promotion process. The method used in this research is the method Profile Matching. This method outlines a process of comparing the actual data values ​​from a profile that will be judged by the value of the expected profile, so it can be the difference competence (also called gap). The results showed that a decision support system Profile Matching method can be used as a tool for the Mandiri Jaya Farm in determining karyaan eligible to get a promotion.